Differences in titin segmental elongation between passive and active stretch in skeletal muscle - DuVall, M. M.; Jinha, A.; Schappacher-Tilp, G.; Leonard, T. R.; Herzog, W. (The Journal of Experimental Biology, 2017)
Since the 1950s, muscle contraction has been explained using a two-filament system in which actin and myosin exclusively dictate active force in muscle sarcomeres. Decades later, a third filament called titin was discovered. This titin filament has recently been identified as an important regulator of active force, but has yet to be incorporated into contemporary theories of muscle contraction. When sarcomeres are actively stretched, a substantial and rapid increase in force occurs, which has been suggested to arise in part from titin-actin binding that is absent in passively stretched sarcomeres. However, there is currently no direct evidence for such binding within muscle sarcomeres. Therefore, we aimed to determine whether titin binds to actin in actively but not in passively stretched sarcomeres by observing length changes of proximal and distal titin segments in the presence and absence of calcium. We labeled I-band titin with fluorescent F146 antibody in rabbit psoas myofibrils and tracked segmental elongations during passive (no calcium) and active (high calcium) stretch. Without calcium, proximal and distal segments of titin elongated as expected based on their free spring properties. In contrast, active stretch differed statistically from passive stretch, demonstrating that calcium activation increases titin segment stiffness, but not in an actin-dependent manner. The consistent elongation of the proximal segment was contrary to what was expected if titin's proximal segment was attached to actin. This rapid calcium-dependent change in titin stiffness likely contributes to active muscle force regulation in addition to actin and myosin.